Geographic Regions for Crop Cost-Return Budgets - Langemeier, Larry N. (My University, 1997)
This publication outlines the regional areas of Kansas for the crop cost-return guides.
MF2235_1997_10
Keywords: MF2235; Economics; Crops; MF